Menstrual Hygiene among Adolescent School Girls of Bhaktapur, Nepal - Rajbhandari, Ajay Kumar; Sagtani, R.A.; GC, K.; Dhaubanjar, R. (Nepal Medical College Journal, 2018)
Adolescence is a transition phase from childhood to womanhood and is marked by onset of menstruation. But, it is still viewed as a religiously impure occurrence in Nepalese society due to social stigma and taboo attached to it. Menstruating females are susceptible to infections and thus, are required to maintain additional hygiene and sanitation. This study tried to explore the existing knowledge and practices on menstrual hygiene among adolescents in Bhaktapur, Nepal.The study included 168 adolescent girls studying in grade nine and ten from four different schools of Bhaktapur Municipality. A self-administered questionnaire developed in local language was used for data collection. These data were entered and analyzed using SPSS-17. Menstruation was considered as a natural physiological phenomenon by 94.6% of the adolescent school girls. Most (93.5%) of the girls used commercially available sanitary pads. The primary source of information on menstruation was their mother however, 35.1% of them reported that they had no prior knowledge on menarche. The major reasons for school absenteeism were discomfort, lack of continuous water supply and shame or fear of staining. Correct knowledge and practice score was not associated with paternal or maternal education while it was negatively correlated with age of adolescents. This study highlights the need to strengthen existing menstruation hygiene management programs in Bhaktapur, Nepal. Emphasis should be laid on providing information to girls who have not experienced menarche and also reinforce it among those who are becoming mature.